2020
DOI: 10.3390/ph13020020
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships (SARs) of α-Ketothioamides as Inhibitors of Phosphoglycerate Dehydrogenase (PHGDH)

Abstract: For many years now, targeting deregulation within cancer cells’ metabolism has appeared as a promising strategy for the development of more specific and efficient cancer treatments. Recently, numerous reports highlighted the crucial role of the serine synthetic pathway, and particularly of the phosphoglycerate dehydrogenase (PHGDH), the first enzyme of the pathway, to sustain cancer progression. Yet, because of very weak potencies usually in cell-based settings, the inhibitors reported so far failed to lay gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
(62 reference statements)
1
7
0
Order By: Relevance
“…Both molecules thus displayed similar binding epitopes, with a high relative saturation transfer for the aromatic hydrogens ( Figure 5 , blue and red) and a lower relative saturation transfer for the morpholine hydrogens ( Figure 5 , light blue and green) suggesting a similar interaction pattern for 2 and 11 with PHGDH. This interesting pattern also explains, at least in part, why modification/substitution of this aromatic ring has a considerable impact on PHGDH inhibition, as previously reported [ 18 ].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Both molecules thus displayed similar binding epitopes, with a high relative saturation transfer for the aromatic hydrogens ( Figure 5 , blue and red) and a lower relative saturation transfer for the morpholine hydrogens ( Figure 5 , light blue and green) suggesting a similar interaction pattern for 2 and 11 with PHGDH. This interesting pattern also explains, at least in part, why modification/substitution of this aromatic ring has a considerable impact on PHGDH inhibition, as previously reported [ 18 ].…”
Section: Resultssupporting
confidence: 80%
“…Early investigations of the structure-activity relationships (SARs) revealed the importance of this para -substitution pattern ( Figure 2 , compare the para -chlorinated derivative 2 and the meta -chlorinated analogue 3 , for instance) [ 14 ]. Moreover, recent studies also demonstrated that structural modifications of the linker and/or the morpholino ring are poorly tolerated and only lead to improved inhibitory potency when coupled with chlorinated para -substitution [ 18 ]. However, at this stage, the precise binding mode of 2 to PHGDH remained mostly unclear.…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl 3 ): δ 10.15 (s, 1H), 7.91 (t, J = 9.2 Hz, 4H), 7.85 (m, 1H), 7.62 (m, 1H), 7.42 (t, J = 7.9 Hz, 2H), 7.35 (d, J = 8.2 Hz, 2H), 7.29 (t, J = 7.5 Hz, 1H), 6.40 (t, J = 3.5 Hz, 1H), 2.44 (s, 3H); 13 C{ 1 H} NMR (100 MHz, CDCl 3 ): δ 187. 4,174.5,145.2,137.8,135.7,131.8,130.1,130.0,129.6,129.1,128.2,127.2,122.2,111.3,21.7;HRMS calcd -4-yl)-2-oxo-N-phenylethanethioamide (3s). Purified by column chromatography (silica gel 200−300 mesh, petroleum ether/ethyl acetate = 3:1), yellow solid, yield: 48% (152 mg), mp: 112.9−113.5 °C.…”
Section: -(2-methoxyphenyl)-2-oxo-n-phenylethanethioamide (3o)mentioning
confidence: 99%
“…3 A representative direct application was reported by Frédérick and co-workers, who found inhibitory activities of α-ketothioamide derivatives on phosphoglycerate dehydrogenase (PHGDH) with implications for cancer cell proliferation. 4…”
Section: Introductionmentioning
confidence: 99%